Penggunaan Diksi dalam Kumpulan Cerita Pendek Shen Congwen dalam Kurun Tahun yang Berbeda - Sinar Anwar; Fenny Salim (Journal of Language, Literature and Teaching, 2019)
The goal of this study was to explore the dictions used in the outstanding compilation of short story written by Shen Congwen and also to find whether there was any changes of dictions made by the author within different year of publication. The short story that became the focus of this study was 棉鞋（MianXie）published in 1925 and传奇不奇（Chuanqi Buqi）published in 1947. This study revealed that 棉鞋（MianXie）in 1925 used 686 dictions which consisted of: denotation 12%, connotation 4%, abstract 5%, general 27%, odd 11%, scientific 21%, popular 18%, slang 2%. Meanwhile, 传奇不奇（Chuanqi Buqi）in 1947 used 1625 dictions which was categorized as denotation 6%, connotation 2%, abstract 4%, general 26%, odd 9%, scientific 28%, popular 23%, and slang 2%.